1990
DOI: 10.1007/bf00170936
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of phenol using an acclimated mixed culture

Abstract: Anaerobic methanogenesis of phenol using mixed cultures derived from cow dung and municipal sewage sludge and adapted to phenol was done in batch reactors. The phenol degradation rate depended on the period in which the culture was acclimated to phenol. Interference in phenol uptake by glucose was observed. Consumption of both phenol and acetic acid was observed when an acetate-adapted culure was used. A phenol-acclimated culture was able to degrade dihydroxy phenols thus indicating the feasibility of cross-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
2
11
0
2
Order By: Relevance
“…the presence of glucose could inhibit utilisation of the target substrate. Satsangee and Ghosh (1990) have also reported that glucose interferes with phenol uptake. In the present study, 0.25 g L -1 glucose was found to be the optimum concentration for phenol degradation.…”
Section: Effect Of Aerationmentioning
confidence: 94%
“…the presence of glucose could inhibit utilisation of the target substrate. Satsangee and Ghosh (1990) have also reported that glucose interferes with phenol uptake. In the present study, 0.25 g L -1 glucose was found to be the optimum concentration for phenol degradation.…”
Section: Effect Of Aerationmentioning
confidence: 94%
“…Thus, while fermentative methanogenic degradation of catechol has been confirmed, the lag phase and end of biodegradation differs enormously, e.g. 0-32 and 6-42 days, respectively [13][14][15]. In other cases, such biodegradation was unsuccessful [17,38].…”
Section: The Need For Standardized Datamentioning
confidence: 98%
“…The lag and end of exponential phases for the other phenolics have also been reported, with the exception of caffeic and gallic acids whose fermentative methanogenesis is given here. For instance, the lag and total biodegradation periods of phenol were 0-6 and 3-49 days, respectively [14,15,29]; for tyrosol 18-28 and 40 days, respectively [16]; for 4-hydroxybenazoic acid 12 and 14 days, respectively [15] and for protocatechuic acid 13 and 14 days, respectively [15].…”
Section: The Need For Standardized Datamentioning
confidence: 99%
See 1 more Smart Citation
“…While the production of ligninolytic enzymes occurs during the secondary metabolism as well as affected by nutrient limitation, the process of degradation occurs after enzyme production. Another study showed that degradation was repressed by glucose, because glucose inhibits the utilization of the target compound (Satsangee and Ghosh, 1990).…”
Section: Biodegradation Of Fluoranthene By Armillaria Sp F022mentioning
confidence: 99%